URGENSI PERSIDANGAN ELEKTRONIK (E-LITIGASI) DALAM PERSPEKTIF HUKUM ACARA PERADILAN AGAMA DI PENGADILAN AGAMA PROBOLINGGO - Sudur, Ishaq Maulana; Meilinda, Fauziyah Putri (USRAH: Jurnal Hukum Keluarga Islam, 2024)
This paper examines the necessity of electronic trials from the standpoint of religious court procedural law in the Probolinggo Religious Court. This article addresses information technology advancements that make e-litigation a viable option for enhancing the effectiveness, accessibility, and timeliness of religious justice processes. By using this technology, parties interested in judicial procedures can receive better services, information sharing can occur more quickly, and geographical obstacles can be reduced. This research examines the religious courts' procedural legal structure, which facilitates the use of computerized trials. In this regard, it is crucial to modify religious court rules to accommodate the requirement for e-litigation in order to prevent normative conflicts and guarantee the legitimacy of online legal proceedings. This study emphasizes how e-litigation may help communities have better access to justice. Electronic litigation has the potential to boost public engagement in the religious justice system by enabling litigants to view and monitor cases over the internet. Data security, privacy protection, and the preparedness of the technological infrastructure to handle possible hazards are given particular emphasis. This article attempts to give a thorough understanding of the use of information technology in the religious justice system by outlining the urgency, legal framework, advantages, and difficulties of e-litigation from the standpoint of religious justice procedural law. It is anticipated that the use of e-litigation would increase the efficacy and efficiency of the legal system, benefiting both religious justice and justice in general. Keywords:  : e-Litigation; Procedural Law of Religious Courts; Religious courts.